APLIKASI PC SMART ORDER by CUSTOM PADA TOKO KOMPUTER BERBASIS ANDROID MENGGUNAKAN METODE LINEAR SEQUENTIAL SEARCH - Sigit Riyadi (LPPM ITB Yadika Pasuruan, 2022)
Abstract : Rapid technological developments have resulted in the availability of more and more data and continues to grow. So that makes data management must be precise and the search algorithm used is very influential on data search. Data that is growing rapidly in very large quantities is often referred to as Big Data. Many use of Android-based ordering applications have implemented Big Data.The Sequential Search method performs a data search by comparing data one by one from a predetermined data set until the data is found, if the data is found, the search will end. The efficiency of the sequential search algorithm can be used to search for random or ordered data with a sequential search process.Making a PC By Custom Ordering Application on an Android-Based Using the Linaer Sequential Search Method is one step to make it easier for customers who want to buy a custom PC using the Android platform with a relatively short data search.